THE INFLUENCE OF BRAND IMAGE AND SELF-IMAGE CONGRUENCE TOWARDS BRAND ATTACHMENT ON FASHION ITEMS (CASE STUDY: STUDENTS OF IBA, SAM RATULANGI UNIVERSITY) - Pangemanan, Ekaristia Gratia; Worang, Frederik G.; Arie, Fitty Valdi (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: As the competitors increase, companies need to secure their customer from moving to other brands. This push companies to be more sensitive with what kind of brand image that can interest customer and urge them to choose the said companiesâ€™ brands. Once the customers feel that a certain brand is relatable to their own needs and wants, it will create an attachment to the said brand. The purpose of this study is to analyze the influence of brand image and self-image congruence toward brand attachment, specifically about fashion items, at International Business Administration, Sam Ratulangi University. The quantitative method is used in this research. In order to collect the data, questionnaires were distributed to 100 IBA students. The result of this research shows that brand image has positive relationship toward brand attachment with significant influence, and self-image congruence also has positive relationship toward brand attachment with significant influence.Â Keywords: brand image, self-image congruence, brand attachmentÂ